GUJARATI LANGUAGE: A SPECIMEN OF INDIAN CULTURE - Upadhyay, Shivani R (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Culture and language are two inseparable entities. Language reflects culture. Rather, it is an important exhibit of culture. Language is shaped by culture and culture is transmitted from one generation to the other through language. Each language has some peculiar characteristics through which it mirrors the culture. One of the most significant features is the vocabulary. The stock of words is the easily available and accessible material reflecting the true colours of any culture. Apart from that, some other features can also be found through the linguistic analysis of the language. This paper intends to show how Gujarati language reflects the Indian culture. This is done through the study of the vocabulary, usage and some intrinsic linguistic features of the language.